2007
DOI: 10.1111/j.1468-3083.2007.02192.x
|View full text |Cite
|
Sign up to set email alerts
|

Thalidomide inhibits human ultraviolet‐B‐induced skin inflammation?

Abstract: Wide excision with margin control or Mohs' surgery must be undertaken if the lesion recurs. For lesions larger than 2.5 cm, Mohs' surgery or wide excision is recommended as first option. 6 In conclusion, the clinical and histopathological recognition of PAK is important in order to apply a more aggressive therapy than the conventional therapy used for the rest of KA subtypes. References1 Salache SJ. Epidemiology of actinic keratosis and squamous cell carcinoma. J Am Acad Dermatol 2000; 42: S4-S7. 2 Naldi L, Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…Intriguingly, it has been shown that thalidomide significantly inhibits UV-induced inflammation in human skin (27,28). This may also provide an explanation for the drug's therapeutic effect in photosensitive diseases such as lupus erythematosus (27,28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, it has been shown that thalidomide significantly inhibits UV-induced inflammation in human skin (27,28). This may also provide an explanation for the drug's therapeutic effect in photosensitive diseases such as lupus erythematosus (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…This may also provide an explanation for the drug's therapeutic effect in photosensitive diseases such as lupus erythematosus (27,28). As UV-induced inflammation in mice and humans is most likely dependent on IL-1 activity (16,23), this raises the possibility that IL-1Ra may be a useful substitute for thalidomide in the treatment of photosensitive disorders.…”
Section: Discussionmentioning
confidence: 99%